Negotiating Islam, Democracy and Pluralism: Islamic Politics and the State in Post-Reform Indonesia - Krismono, Krismono; Abdi, Supriyanto; Syahmirwan, Syahmirwan (Mazahib, 2025)
The question of how democratic states navigate religious aspirations remains central in Muslim-majority societies. In Indonesia, this relationship has followed a nonlinear trajectory shaped by political alliances, institutional asymmetries, and ideological transformations. This article explores how successive governments—from Habibie to Joko Widodo—have managed the complex intersection of Islam, democracy, and pluralism. Using a qualitative comparative approach, it identifies shifts in state strategies toward Islamic political expression, ranging from symbolic inclusion to legal restriction and bureaucratic regulation. The concept of contested accommodation is proposed to explain how Islamic norms have been selectively engaged, redirected, or constrained through evolving institutional mechanisms. While some administrations prioritized inclusive pluralism, others aligned with conservative religious agendas. Populist religiosity, transnational influences, and media amplification further shaped the policy landscape. The findings suggest that Islamic political expression in Indonesia is neither fully absorbed nor rejected, but continually renegotiated. Pluralism, in this context, is sustained not through ideological consensus but through ongoing recalibration within democratic institutions.